NOVEL MFRP MUTATION WITH NANOPHTHALMOS, OPTIC DISK DRUSEN, AND PERIPHERAL RETINOSCHISIS IMAGED WITH ULTRA-WIDEFIELD OPTICAL COHERENCE TOMOGRAPHY. Issue Volume 17:Issues 3(2023) (May 2023) - Kovacs, Kyle D.; Van Tassel, Sarah H.; Gupta, Mrinali P.
Abstract : An asymptomatic patient presented with bilateral nanophthalmos, optic disk drusen, and foveal hypoplasia without foveoschisis, cataract, and occludable angles. Salivary genetic testing revealed homozygosity of a novel mutation of the MFRP gene consistent with a clinically distinct phenotype of autosomal recessive nanophthalmos. Ultra-widefield optical coherence tomography demonstrated extensive multilevel peripheral retinoschisis. Abstract : Purpose: To describe with multimodal imaging including the use of ultra-widefield optical coherence tomography imaging a distinct phenotype of autosomal recessive nanophthalmos associated with a novel mutation of the MFRP gene (membrane-type frizzled-related protein). Methods: Case report of a single patient followed by the Weill Cornell Medicine Department of Ophthalmology Retina and Glaucoma Services, and review of the relevant literature. Results: A patient with a novel homozygous mutation in the MFRP gene (c.472C>T) presented with nanophthalmos, optic disk drusen, foveal hypoplasia, and extensive peripheral retinoschisis, which was revealed to be multilevel retinoschisis on ultra-widefield optical coherence tomography. Unlike other reported cases, the findings associated with this novel mutation did not include foveoschisis or clinically obvious retinitis pigmentosa. The patient underwent prophylactic peripheral laser iridotomy in both eyes. Conclusion: Here, we present a patient with nanophthalmos, optic disk drusen, and foveal hypoplasia associated with extensive peripheral retinoschisis imaged by ultra-widefield optical coherence tomography, but not foveal retinoschisis or prominent retinitis pigmentosa. The findings may expand the clinical spectrum of MFRP -associated nanophthalmos.